KETERAMPILAN KOMUNIKASI PADA PEMBELAJARAN FISIKA SECARA DARING DI KELAS X SMA - Khasanah, Khamidatul (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to determine the level of student communication skills during online learning. The subjects of this study were 40 students of class X MIPA SMA N 1 Bangsri. This research was conducted in April-May 2021 using a qualitative descriptive method. The data collection tool uses a questionnaire via the google form link. The questionnaire refers to 5 indicators, namely: creating an atmosphere during discussion, adjusting word choice, volume and voice intonation, conveying ideas/results clearly, effectively and systematically, being able to see the ability of their friends to communicate, and being able to evaluate the material. The results of this study indicate that students' communication skills are 28% in the low category.